The Use of Project-Based Learning Strategies in Improving Students’ English Writing Skills at STIKes RS Husada: The Implementation and Students’ Opinion - Ludovikus, Ludovikus; Hardin La Ramba; Ribka Sabarina Panjaitan; Yurita Mailintina; Christopher Paul Lynch (Jurnal EduHealth, 2023)
Writing becomes the most challenging skill for the students as it needs more time to develop and tend to raise problem to students. Therefore, project-based learning is offered to solve the problems in writing. Some experts believe that project-based learning (PBL) can provoke the students to get new knowledge through their own project. This research reports on the implementation of project-based learning in teaching writing. The objectives of the research are to know the implementation of project-based learning in elevating the students’ ability on writing and to know the students’ opinion of the implementation of project-based learning in teaching writing. Qualitative was used as a research method and classroom action research as a research design. The participants of the research were third semester students in one interview. Then, data were analyzed based on triangulation. As result, it was found that the implementation during the implementation of this method as they gave positive opinion toward the method used; they project give engaged the students in solving a real problem and answering it. In other word, this project could develop the students’ critical thinking and it could be a meaningful project for them.